Boodiversita delle Aleocharinae delle Cina: Athetini, Parte seconda, Generi Aloconota e Liogluta (Coleoptera, Staphylinidae). - Pace, Roberto (Contributions to Entomology = Beiträge zur Entomologie, 2011)
Taxonomic study of 2 genera of the tribe Athetini: Aloconota and Liogluta. 27 new species are described and illustrated, of which 13 Aloconota (A. heilongjiangensis n. sp., A. dabamonticola n. sp., A. houzhenziensis n. sp., A. erlangmontis n. sp., A. profunda n. sp., A. levitatis n. sp., A. sinoripicola n. sp., A. diancangensis n. sp., A. sinocarinifera n. sp., A. hubeicola n. sp., A. sinica n. sp., A. sinolongula n. sp., A. insulsitatis n. sp.) and 14 Liogluta (L. muyupingensis n. sp., L. kandingensis n. sp., L. shalulinigra n. sp., L. tibetana n. sp., L. qinlingensis n. sp., L. dailangensis n. sp., L. magnumforamen n. sp., L. shaluliensis n. sp., L. rostrumaquilae n. sp., L. sinotruncata n. sp., L. sinoclaripennis n. sp., L. qionglaiensis n. sp., L. qionglaimontis n. sp., L. erlangicola n. sp.). Additional data are reported for 16 species. Two new combinations and a new synonymy are proposed. Sommario Studio tassonomico di 2 generi della tribù Athetini: Aloconota e Liogluta. Sono descritte e illustrate 27 nuove specie, di cui 13 Aloconota (A. heilongjiangensis n. sp., A. dabamonticola n. sp., A. houzhenziensis n. sp., A. erlangmontis n. sp., A. profunda n. sp., A. levitatis n. sp., A. sinoripicola n. sp., A. diancangensis n. sp., A. sinocarinifera n. sp., A. hubeicola n. sp., A. sinica n. sp., A. sinolongula n. sp., A. insulsitatis n. sp.) e 14 Liogluta (L. muyupingensis n. sp., L. kandingensis n. sp., L. shalulinigra n. sp., L. tibetana n. sp., L. qinlingensis n. sp., L. dailangensis n. sp., L. magnumforamen n. sp., L. shaluliensis n. sp., L. rostrumaquilae n. sp., L. sinotruncata n. sp., L. sinoclaripennis n. sp., L. qionglaiensis n. sp., L. qionglaimontis n. sp., L. erlangicola n. sp.). Sono riferiti dati aggiuntivi per 16 specie. Sono proposte due nuove combinazioni e una nuova sinonimia. Keywords Coleoptera, Staphylinidae, Aleocharinae, taxonomy, China. Nomenclatural Acts dabamonticola Pace, 2011 (Aloconota), spec. nov. diancangensis Pace, 2011 (Aloconota), spec. nov. erlangmontis Pace, 2011 (Aloconota), spec. nov. heilongjiangensis Pace, 2011 (Aloconota), spec. nov. houzhenziensis Pace, 2011 (Aloconota), spec. nov. hubeicola Pace, 2011 (Aloconota), spec. nov. insulsitatis Pace, 2011 (Aloconota), spec. nov. levitatis Pace, 2011 (Aloconota), spec. nov. longwangensis (Pace, 1998) (Aloconota), comb. nov. hitherto Hydrosmecta longwangensis Pace, 1998 profunda Pace, 2011 (Aloconota), spec. nov. pulchricarinata Pace, 2004 (Aloconota), syn. nov. of Aloconota invisa Pace, 1987 rougemonti (Pace, 1998) (Aloconota), comb. nov. hitherto Hydrosmecta rougemonti Pace, 1998 sinica Pace, 2011 (Aloconota), spec. nov. sinocarinifera Pace, 2011 (Aloconota), spec. nov. sinolongula Pace, 2011 (Aloconota), spec. nov. sinoripicola Pace, 2011 (Aloconota), spec. nov. dailangensis Pace, 2011 (Liogluta), spec. nov. erlangicola Pace, 2011 (Liogluta), spec. nov. kandingensis Pace, 2011 (Liogluta), spec. nov. magnumforamen Pace, 2011 (Liogluta), spec. nov. muyupingensis Pace, 2011 (Liogluta), spec. nov. qinlingensis Pace, 2011 (Liogluta), spec. nov. qionglaiensis Pace, 2011 (Liogluta), spec. nov. qionglaimontis Pace, 2011 (Liogluta), spec. nov. rostrumaquilae Pace, 2011 (Liogluta), spec. nov. shaluliensis Pace, 2011 (Liogluta), spec. nov. shalulinigra Pace, 2011 (Liogluta), spec. nov. sinoclaripennis Pace, 2011 (Liogluta), spec. nov. sinotruncata Pace, 2011 (Liogluta), spec. nov. tibetana Pace, 2011 (Liogluta), spec. nov.